Kegiatan Keagamaan dan Pamali Hari Kamis Berjualan di Kabupaten Pasuruan - Agus Purnomo Ahmad Putikadyanto; Nur Aisyah Sefrianah (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2019)
In Pasuruan Regency, on Thursday many shops and stalls were closed. Thursday is considered a good day for various religious activities. This study aims to describe the relevance, history, and implementation of religious activities and Pamali Thursday sales in Pasuruan Regency. This research is a qualitative research with a phenomenological type to describe the phenomena that occur in Pasuruan Regency. The data source of this study were representatives of community leaders, sellers, and consumers in Pasuruan Regency with interview and observation data collection techniques. The results showed that many shops or stalls closed Thursday in Pasuruan Regency because there was an assumption Thursday that it was a good day to send prayers to families who had died. The shops and stalls that are closed in Pasuruan Regency are related to religious activities, namely sending prayers to dead relatives. This tradition has been around for a long time and has been passed down for generations. Thursday is filled with religious activities such as takziah to the tomb, recitation, istighosah, reading yasin and tahlil. Not all shops and stalls close on Thursday. Usually closed are small to medium scale shops or stalls with local Muslim owners.